2004
DOI: 10.1385/bter:98:2:109
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Manganese, Selenium, Zinc, Copper, and Iron Concentrations in Patients with Schizophrenia

Abstract: A number of essential trace elements play a major role in various metabolic pathways. Selenium (Se), manganese (Mn), copper (Cu), zinc (Zn), and iron (Fe) are essential trace elements that have been studied in many diseases, including autoimmune, neurological, and psychiatric disorders. However, the findings of previous research on the status of trace elements in patients with schizophrenia have been controversial. We studied these elements in patients with a DSM-IV diagnosis of schizophrenia and compared them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 28 publications
3
62
1
1
Order By: Relevance
“…Arinola et al found significantly higher values of Zn in patients with schizophrenia who were on antipsychotic medication than in controls (26). Yanik et al also found that Zn levels in patients with schizophrenia were higher than in controls; however the difference was not statistically significant (15). Olabanji et al also found increased levels of serum Zn in patients with schizophrenia compared to controls (27).…”
Section: Serum Zinc and Copper Levels In Schizophreniamentioning
confidence: 98%
See 1 more Smart Citation
“…Arinola et al found significantly higher values of Zn in patients with schizophrenia who were on antipsychotic medication than in controls (26). Yanik et al also found that Zn levels in patients with schizophrenia were higher than in controls; however the difference was not statistically significant (15). Olabanji et al also found increased levels of serum Zn in patients with schizophrenia compared to controls (27).…”
Section: Serum Zinc and Copper Levels In Schizophreniamentioning
confidence: 98%
“…However, plasma Cu concentrations were shown to be elevated in patients with schizophrenia and a study of trace metals in scalp hair samples of patients with schizophrenia has shown an increase in Cu concentrations (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, serum Cu levels were higher in schizophrenics compared to the control group. There are various studies reporting high Cu levels in schizophrenics (5,26). This result may be explained by the inhibition of Zn re-uptake by neuroleptics and an antagonistic relationship between Zn and Cu concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated that serum copper and ceruloplasmin levels were decreased or remained the same, while others have indicated an increase in the serum levels of their metabolites [18][19][20][21] . Diverse results have been reported in patients with autism.…”
Section: Introductionmentioning
confidence: 99%